Analisis Ketahanan Hidup Pada Penderita Kanker Serviks Menggunakan Regresi Cox Proportional Hazard - Ummi Hafildah; Ria Dhea Layla Nur Karisma (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
Survival analysis is a statistical method used to analyze data with time until the occurrence of a certain event which is commonly referred to as